2010
DOI: 10.1111/j.1365-2788.2010.01346.x
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis in people with intellectual disabilities: a review and a brief study of risk factors for osteoporosis in a community sample of people with intellectual disabilities

Abstract: We conclude that we should be screening for the risk factors associated with low BMD in adults with ID. If these are present further investigations should take place and those found to have osteoporosis and osteopenia should have treatment at an early stage to prevent morbidity and improve their quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
1
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(110 citation statements)
references
References 40 publications
5
91
1
13
Order By: Relevance
“…Antipsychotics use in autistic children has been associated with significantly increased weight gain compared to placebo controls (McCracken, McGough et al 2002;Shea, Turgay et al 2004). Antiepileptics have been associated with osteoporosis (Srikanth, Cassidy et al 2011) and sleep problems (van de Wouw, Evenhuis et al…”
Section: Discussionmentioning
confidence: 99%
“…Antipsychotics use in autistic children has been associated with significantly increased weight gain compared to placebo controls (McCracken, McGough et al 2002;Shea, Turgay et al 2004). Antiepileptics have been associated with osteoporosis (Srikanth, Cassidy et al 2011) and sleep problems (van de Wouw, Evenhuis et al…”
Section: Discussionmentioning
confidence: 99%
“…Low bone mineral density, osteoporosis, osteopenia and fractures have all been found at higher prevalence rates in people with learning disabilities as compared to the general population (Srikanth et al, 2011). Lin et al (2014) reported that in a sample of individuals with learning disability over the age of 40 more than half had either osteoporosis or osteopenia.…”
Section: Bone Health In People With a Learning Disabilitymentioning
confidence: 99%
“…A osteoporose (OP) é uma doença sistêmica esquelética caracterizada por baixa massa óssea e deterioração da micro-arquitetura do tecido ósseo, com conseqüente aumento da fragilidade óssea e suscetibilidade à fratura (Angelopoulou et al, 2000;Tyler Jr et al, 2000;Múgica et al, 2002;Keiserman, 2008;Taguchi et a., 2008;Sociedade Brasileira de Reumatologia, 2011;Srikanth et al, 2011;Taguchi et al, 2011;Kavitha et al, 2012).…”
Section: Osteoporoseunclassified
“…A OP pode ser classificada de acordo com o fator de risco associado ao seu desenvolvimento, sendo os principais tipos: OP senil e OP pós menopausa (que correspondem a 80% das OP), e OP secundária (que corresponde a 20% das OP) (Sociedade Brasileira de Reumatologia, 2001;Keiserman, 2008 Tyler Jr et al, 2000;Brandão et al, 2009;Srikanth et al, 2011).…”
Section: Fatores De Risco Para O Desenvolvimento Da Osteoporoseunclassified
See 1 more Smart Citation